Improved compliance of midwives with stillbirth prevention and control practices after creating and implementing an educational program in a Chinese obstetric clinic - Xueheng Wen; Jinguo Zhai; Hamza Saidi Lilenga; Xueyan Wang (BMC Medical Education)
Abstract Background This study evaluated midwives’ compliance with evidence-based stillbirth prevention practices and the impact of a targeted educational intervention. Five audit criteria were established based on the Safer Baby Bundle and expert consensus: (1) smoking cessation support, (2) fetal growth restriction (FGR) screening, (3) fetal movement education for decreased fetal movement, (4) promotion of safe late-pregnancy sleep positions, and (5) risk-based birth timing decisions. Methods Using the Joanna Briggs Institute’s Practical Application of Clinical Evidence System (PACES) framework, data from 61 midwives in a Chinese obstetric clinic were collected via baseline and follow-up audits. Five audit criteria were established to determine midwives’ compliance to best practices for stillbirth prevention. Results Baseline compliance showed 100% adherence to FGR screening (criterion 2), while criteria 1, 3, 4, and 5 had 0% compliance. Following the intervention,, all criteria achieved 100% compliance, with significant improvements in previously non-compliant areas. Conclusions The educational program effectively improved midwives’ compliance with key stillbirth prevention practices. Integrating such interventions into midwifery education and clinical workflows is essential to reduce preventable stillbirths.